The Ministering Critic: Kierkegaard's Theology of Communication - Johnson, Russell (Religions, 2020)
This paper analyzes Kierkegaard's scattered writings on communication to foreground the distinctively theological dimension of Kierkegaard's rhetorical theory. "Indirect communication" needs to be understood as a strategy to address a specific theological problem, namely, the tendency for readers who think they are already Christian to dismiss or domesticate rhetoric that summons them to authentic Christian existence. Since Christianity is an "existence-communication," the questions of what it means to be a Christian and how one can faithfully communicate Christianity are integrally linked for Kierkegaard. Contemporary apologists, activists, and preachers who rely on more direct modes of communication to express the Christian gospel have much to learn from Kierkegaard's grappling with the illusions that beset Christian witness.